ANALISIS PERTUMBUHAN EKONOMI DAN INDEKS GINI KABUPATEN SUMEDANG - Sumaryana, Fitriana Dewi; Sugito Putra, Toufiq Agung Pratomo; Hakim, Abdul; Jaka Sudewa (IKOPIN, 2022)
This study aims to analyze the level of income inequality by using the Gini Ratio Index approach. Sources of data used in this study are primary and secondary data obtained through observation and data collection reports sourced from the Central Statistics Agency (BPS) of Sumedang Regency and the Regional Development Planning Agency (BAPPPEDA) of Sumedang Regency, such as the Regency in Figures and the Welfare indicators from the Census. National. Data sourced from Bappeda and BPS in the form of data on Gross Regional Domestic Product per capita on the basis of constant prices, and consumption data on average consumption per capita. The results showed that economic growth as seen from the GRDP indicator on the basis of constant prices decreased in 2020 due to the Covid-19 pandemic. The Gini Index of Sumedang Regency for the period 2016 – 2020 is in the moderate category (> 0.384) or at a moderate level.